PENGARUH PEMAHAMAN PAJAK, SOSIALISASI PAJAK, DAN NORMA SUBJEKTIF TERHADAP KESADARAN PAJAK MAHASISWA PELAKU USAHA - Sukmayana, Ketut Krisnanda Dewi; Hasibuan, Henny Triyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024DO - 10.24843/EEB.2024.v13.i11.p14, 2024)
In order to increase tax revenue, the Ministry of Finance together with the Directorate General of Taxes are currently inviting the younger generation, especially students, to increase their understanding and awareness of taxes. This is targeted on students because as seen from the existing phenomenon there has been an increase in young business actors from the students themselves, so guidance is needed for students to realize their tax obligations from an early age. The purpose of this study was to determine the effect of tax understanding, tax socialization, and subjective norms on tax awareness of business students. This research was conducted at the Wida Community, Faculty of Economics and Business, Udayana University with a saturated sample method of 43 people. Data collection was conducted using a questionnaire using google form. The data collected was then processed using Statistical Package for the Social Sciences (SPSS) with multiple linear regression analysis techniques. The results of the study show that tax understanding and tax socialization have a positive and significant effect on the tax awareness of business students. However, subjective norm variables which are categorized into family, lecturers, and relatives have no role in influencing the level of tax awareness of business actors students.